2016
DOI: 10.5367/te.2015.0538
|View full text |Cite
|
Sign up to set email alerts
|

Competition, market structure and market power within the hotel-supplier sector in Antalya, Turkey

Abstract: Today’s competitive business environment forces companies of all sorts to strive for a larger market share. Globalization has played a major role in accelerating this trend. This article explores the market structures that apply to hotel suppliers in Antalya, the leading international beachside resort on Turkey’s south-coast region. Focusing on market competitiveness, this article examines eight major product subcategories that are offered by 206 suppliers to 21 hotels across the region. The study examines the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Tourism specialization in a province is the key determinant of hotel industry efficiency and reflects regional factors. Market competition has been shown by research to have both positive and negative impacts on hotel industry efficiency in different cases (Assaf et al, 2017;Göcen et al, 2017;Huang et al, 2012); therefore, this research also confirms that including regional factors such as tourism specialization contributes to the in-depth and contextual understanding of this relationship.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Tourism specialization in a province is the key determinant of hotel industry efficiency and reflects regional factors. Market competition has been shown by research to have both positive and negative impacts on hotel industry efficiency in different cases (Assaf et al, 2017;Göcen et al, 2017;Huang et al, 2012); therefore, this research also confirms that including regional factors such as tourism specialization contributes to the in-depth and contextual understanding of this relationship.…”
Section: Discussionsupporting
confidence: 74%
“…These three studies have a common methodology with a linear perspective. However, as Göcen et al (2017) argued, given increased lodging demand derived from the boosting tourism industry in destinations, market competition among hotels becomes more fierce because more competitors swarm into the market. Moreover, Assaf et al (2017) found evidence that intense competition could harm the performance of hotels.…”
Section: The Determinants Of Hotel Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…It generates consumer confidence, regional reputation, and recognition of excellence (Rendleman et al, 2016). Qualified labor is required to guarantee the quality of services and Tourism research Proposed an integrated regional computer information management system, a strategic tool for developing tourism and SMEs Foster et al (2018) Explored the importance of digital connectivity in global value chains Göçen et al (2017) Observed the influence of technology and innovation to select suppliers Innovation Kallmuenzer (2018) Identified the actors that drive innovation in family companies of the hospitality sector Mykola et al (2020) Discusses the implementation of innovative projects for investments in tourism Labor costs Aitken and Hall (2000) Observed that foreign skills will affect a company's human resources policy, educational institutions and immigration policy Dewhurst et al (2007) Identified the SMEs problems regarding the offering of training programs Performance Bedradina and Nezdoyminov (2019) Compared the quality of the tourism product components with similar features offered in the same market segment Camison and Fores (2015) Developed an explanatory model for the determinants of tourism competitiveness exploring the different external forces and internal factors Fotiadis et al (2014) Identified the main factors for business efficiency perceived by entrepreneurs in rural tourism: local leadership and synergistic support from the government Hallak et al (2012) Demonstrated the relevance of the place identity for the entrepreneur, management of tourism and business performance Peters et al (2019) Identified the main factors of quality of life perceived by hospitality entrepreneurs and the effect on business growth Rendleman et al (2016) Identified the main factors that increase or restrict the competitive performance of the wine business Williams and Peters (2008) Examined aboriginal tourism companies' operational characteristics and challenges Yang and Cai (2016) Emphasized the links between the performance of the hospitality industry and regional features Yang et al (2017) Evaluated the hotel industry's performance based on efficiency, incorporating sector and regional factors Zapalska and Brozik (2013) Found that concentrating on a single business and innovation are success factors in tourism SMEs Pricing policies Buiga et al (2017) Presented a pricing model as strategy for promotion and innovation based on the marginal contribution of attributes Pellinen (2003) Observed that price decisions are made in regional and inter-regional networks of tourist companies Sustainability…”
Section: Tourism Researchmentioning
confidence: 99%
“…Although the majority of studies about supplier selection focus on manufacturing industry, the importance of this phenomenon has also been discussed in the context of service industry. Göçen et al (2017) have interviewed hotel managers in Antalya and determined that product quality, cost, price and delivery are the most important factors to select suppliers in tourism industry. Davras and Karaatlı (2014) reliability and references to this list.…”
Section: Literature Reviewmentioning
confidence: 99%